Strategy of stock valuation by fundamental analysis - Suzana Baresa; Sinisa Bogdan; Zoran Ivanovic (UTMS Journal of Economics, 2013)
Common stock valuation presents one of the most complex tasks in financial analysis. When it attempts to answer on question: 'what causes stock price movements? 'Then the answer would not relate only on economic factors. There are numerous factors that affect the stock price and they are almost impossible to predict. As one of the best ways to fight against many factors that make the uncertainty, arises fundamental analysis. Fundamental analysis is one of the most widely used methods for estimating price movements of securities which essentially analyses the impact of micro and macro-economic factors on the business of the corporation in order to predict future economic and financial effects. Fundamental analysis also examine various financial statements with the aim to asses a real value of company's stock. This work has the task to systematize knowledge about fundamental analysis, so it can serve as a good base for future research.
Keywords: G10; 330; fundamental analysis; financial indicators; intrinsic value; discount models; stocks